Evidence for the existence of downward real earnings management - Bill Francis; Iftekhar Hasan; Lingxiang Li (Bank of Finland, 2015)
​Prior studies of real-activity earnings management (REM) focus on earnings-inflating abnormal activities. We seek to establish the existence of downward REM by investigating several corporate events in which managers have incentives to temporarily deflate market valuations. Specifically, we focus on, and find downward REM before, share repurchases, management buyouts (MBOs), and CEO option awards. Large-sample evidence of downward REM is also found in our general analysis of earnings smoothing. Downward REM becomes much smaller or nonexistent when there is a lack of managerial incentives in those events, such as non-carry-through repurchases, incomplete MBOs, and unexpected option awards. Following the research design of Zang (2012), we find that various REM and AEM cost factors consistently influence the magnitude of downward REM and AEM around the three corporate events.
URN:NBN:fi:bof-201508131351
Keywords: 330